Psychometric Properties of the Cognitive Emotion Regulation Questionnaire (CERQ) in Patients with Fibromyalgia Syndrome - Feliu-Soler, Albert; Reche-Camba, Elvira; Borràs, Xavier; Pérez-Aranda, Adrián; Andrés-Rodríguez, Laura; Peñarrubia-María, María T.; Navarro-Gil, Mayte; García-Campayo, Javier; Bellón, Juan A.; Luciano, Juan V. (Frontiers in Psychology, 2017)
Given that Fibromyalgia Syndrome (FMS) is associated with problems in emotion regulation, the importance of assessing this construct is widely acknowledged by clinical psychologists and pain specialists. Although the Cognitive Emotion Regulation Questionnaire (CERQ) is a self-report measure used worldwide, there are no data on its psychometric properties in patients with FMS. This study analysed the dimensionality, reliability, and validity of the CERQ in a sample of 231 patients with FMS. Given that “fibrofog” is one of the most disabling FMS symptoms, in the present study, items in the CERQ were grouped by dimension. This change in item presentation was conceived as an efficient way of facilitating responses as a result of a clear understanding of what the items related to each dimension are attempting to measure. The following battery of measures was administered: the CERQ, the Revised Fibromyalgia Impact Questionnaire, the Pain Catastrophizing Scale, the Center for Epidemiologic Studies Depression Scale, and the State-Trait Anxiety Inventory. Four models of the CERQ structure were examined and confirmatory factor analyses supported the original factor model, consisting of nine factors – Self-blame, Acceptance, Rumination, Positive refocusing, Refocus on planning, Positive reappraisal, Putting into perspective, Catastrophizing, and Other-blame. There was minimal overlap between CERQ subscales and their internal consistency was adequate. Correlational and regression analyses supported the construct validity of the CERQ. Our findings indicate that the CERQ (items-grouped version) is a sound instrument for assessing cognitive emotion regulation in patients with FMS.